Technical issues stemming from endoscopic-ultrasound-guided gallbladder drainage: A single center experience - Kanno, Yoshihide; Kozakai, Fumisato; Koshita, Shinsuke; Ogawa, Takahisa; Kusunose, Hiroaki; Masu, Kaori; Sakai, Toshitaka; Murabayashi, Toji; Ito, Kei (Turkish Journal of Gastroenterology, 2019)
Background/Aims: This study was conducted to evaluate the outcomes of endoscopic-ultrasound-guided gallbladder drainage (EUS-GBD) using traditional biliary stents without lumen-apposing stents and to determine technical issues. Materials and Methods: All 18 patients who underwent EUS-GBD at our center between 2012 and 2018 were evaluated. After the clinical outcomes (including technical success, clinical effectiveness, adverse events, and recurrence) were analyzed, technical countermeasures for problems extracted from the analysis were developed. Results: The rates of technical success, clinical effectiveness, severe adverse event occurrence, and recurrence of acute cholecystitis were 94% (17/18), 88% (15/17), 6% (1/18, massive bile leakage), and 27% (4/15), respectively. Distal gastrectomy causing scope instability, the non-swollen gallbladder, and double pigtail stent use caused technical difficulties. A fully covered metal stent (fcMS) should be placed in a shallow position so that it does not wedge into the opposite site. When the puncture route involves the gastric wall, the proximal portion of an fcMS located in the stomach can migrate toward the abdominal cavity. Conclusion: Although the clinical outcomes of EUS-GBD were relatively favorable, several technical issues related specifically to EUS-GBD were observed. Technical countermeasures would improve the outcomes.